The effect of slightly warm temperature on work performance and comfort in open‐plan offices – a laboratory study. (7th May 2015) - Maula, H.; Hongisto, V.; Östman, L.; Haapakangas, A.; Koskela, H.; Hyönä, J.
Abstract: The aim of the study was to determine the effect of a temperature of 29°C on performance in tasks involving different cognitive demands and to assess the effect on perceived performance, subjective workload, thermal comfort, perceived working conditions, cognitive fatigue, and somatic symptoms in a laboratory with realistic office environment. A comparison was made with a temperature of 23°C. Performance was measured on the basis of six different tasks that reflect different stages of cognitive performance. Thirty‐three students participated in the experiment. The exposure time was 3.5 h in both thermal conditions. Performance was negatively affected by slightly warm temperature in the N‐back working memory task. Temperature had no effect on performance in other tasks focusing on psychomotor, working memory, attention, or long‐term memory capabilities. Temperature had no effect on perceived performance. However, slightly warm temperature caused concentration difficulties. Throat symptoms were found to increase over time at 29°C, but no temporal change was seen at 23°C. No effect of temperature on other symptoms was found. As expected, the differences in thermal comfort were significant. Women perceived a temperature of 23°C colder than men.